How poems get made - Longenbach, James (W.W. Norton & Company, 2018)
"Each of the twelve chapters of How Poems Get Made examines a specific aspect of the poetic medium: diction, syntax, rhythm, echo, figure, repetition, and more. Acclaimed poet and critic James Longenbach shows how a poet may manipulate these most basic elements of diction and syntax to create voice, image, tone, or song, and bring a poem to life. Why does a great lyric poem ask to be reread, even after we know it by heart? In How Poems Get Made, Longenbach answers this question by discussing a wide spectrum of exemplary poems, from Shakespeare through Dickinson, Stevens, and Moore, to a variety of poets making poems today. How Poems Get Made is the perfect guide both in the classroom and beyond. Longenbach's clear, wise lessons are essential to anyone interested in composing or appreciating a poem"--